A Response to Frequently Asked Questions about the 2018 Lake Okeechobee, Caloosahatchee and St. Lucie Rivers and Estuaries Algal Blooms - Lisa S. Krimsky; Edward J. Phlips; Karl Havens (EDIS)
Heavy rainfall with Hurricane Irma in 2017 and a rainy spring in 2018 set the stage for large-scale summer algal blooms in Lake Okeechobee and the St. Lucie and Caloosahatchee Rivers and Estuaries. Concerned residents and visitors flocked to social media. Authors Lisa Krimsky, Ed Phlips, and Karl Havens read their posts and tweets and now respond to concerns and questions about algal blooms in this 7-page fact sheet published by UF/IFAS Extension and the Florida Sea Grant College Program. http://edis.ifas.ufl.edu/sg159